ANALISIS PERBANDINGAN PERFORMA POINT-TO-POINT TUNNELING PROTOCOL DAN ETHERNET OVER INTERNET PROTOCOL DALAM MEMBENTUK VPN - Robby Triadi Susanto; Gani Indriyanta; R. Gunawan Santosa (Universitas Kristen Duta Wacana, 2013)
Virtual Private Network (VPN) is a technology implemented as a solution to connect head and branch offices through a network. VPN enables all offices connected to be treated as a single broadcast domain or a single network, providing a private connection. VPN can be implemented over several protocols: Point-To-Point Tunneling Protocol (PPTP) and Ethernet over Internet Protocol (EoIP). This research conducted through implementation of both protocols on a site-to site VPN and measuring each protocol’s performance using throughput, packet loss and delay parameters obtained from real topology. Overall result shows that EoIP performs better than PPTP. Within six days of observation, obtained data shows that EoIP has better throughput and less delay than PPTP, while PPTP has a smaller rate of packet loss than EoIP.